2016
DOI: 10.1161/atvbaha.116.307883
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Factor Xa and Protease-Activated Receptor 2 as Novel Therapeutic Targets for Diabetic Nephropathy

Abstract: Objective-The role of hypercoagulability in the pathogenesis of diabetic nephropathy (DN) remains elusive. We recently reported the increased infiltration of macrophages expressing tissue factor in diabetic kidney glomeruli; tissue factor activates coagulation factor X (FX) to FXa, which in turn stimulates protease-activated receptor 2 (PAR2) and causes inflammation. Approach and Results-Here, we demonstrated that diabetes mellitus increased renal FX mRNA, urinary FXa activity, and FX expression in glomerular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(113 citation statements)
references
References 49 publications
6
98
0
Order By: Relevance
“…16 FXa stimulates proteaseactivated receptor 2 (PAR2). 17 The activation of PAR2 promotes pro-inflammatory activation of macrophages, as determined by inflammatory molecule expression and foam cell formation, which promotes vascular inflammation. 18 The direct thrombin inhibitor also inhibits the expression of pro-inflammatory markers.…”
Section: Anti-inflammatory Effect Of Doacmentioning
confidence: 99%
“…16 FXa stimulates proteaseactivated receptor 2 (PAR2). 17 The activation of PAR2 promotes pro-inflammatory activation of macrophages, as determined by inflammatory molecule expression and foam cell formation, which promotes vascular inflammation. 18 The direct thrombin inhibitor also inhibits the expression of pro-inflammatory markers.…”
Section: Anti-inflammatory Effect Of Doacmentioning
confidence: 99%
“…Furthermore, cross-talk occurs between PAR1/2 signaling and TGF-β signaling, which links to tissue fibrosis [31,32]. PAR1/2 deficiency has been reported to be protective against experimental renal ischemia-reperfusion injury [33], crescentic GN [34], diabetic nephropathy [35,36], and unilateral ureteral obstruction [37,38]. TM reportedly plays a role in PAR activation, with thrombin no longer converting fibrinogen to fibrin or activating PAR1 when it binds to the EGF-like domains of TM [1].…”
Section: Discussionmentioning
confidence: 99%
“…PAR2 increases cytokine or chemokine production through mitogen-activated protein kinase or nuclear factor kappa B signaling (Rothmeier and Ruf 2012;Vesey et al 2013). In murine kidney disease models, genetic deletion or pharmacological inhibition of PAR2 improves diabetic kidney disease (DKD), glomerulonephritis, renal fibrosis, and cisplatin nephrotoxicity through inflammatory cytokine or profibrotic mediator reduction (Moussa et al 2007;Kumar Vr et al 2016;Oe et al 2016;Hayashi et al 2017;Watanabe et al 2019). On the other hand, in a recent study, we demonstrated that a deficiency of PAR2 aggravates vascular endothelial growth factor inhibitor-induced glomerular injury (Oe et al 2019).…”
Section: Introductionmentioning
confidence: 94%
“…at 95℃ for 5s and annealing and extension at 60℃ for 15s. We have published the primer sequences in our previous reports (Li et al 2010;Oe et al 2016).…”
Section: Quantitative Real-time Polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%
See 1 more Smart Citation